Response to Graves-Basedow Disease treatment in pediatric patients - Calagua Quispe, Martha (2014)
Objectives: To describe the clinical and biochemical response to treatment of hyperthyroidism. Design: Retrospective study. Setting: Instituto Nacional de Salud del Niño, Lima, Peru. Participants: children. Methods: From 1996 to 2007 32 patients with diagnosis of hyperthyroidism were studied. Remission was defined when patients were asymptomatic and biochemically euthyroid 6 months after the end of treatment; relapse when altered hormone levels were found after this period of time. Main outcome measures: Remission or relapse following treatment. Results: Mean age at diagnosis was 10.5 years (3.2-17.9 years), 26 patients (81.2 %) were female; 13 (40.6 %) were pubertal and 18 (59.3%) prepubertal. The most frequent symptoms and signs were: goiter, sweating, nervousness, weight loss, tachycardia and exophthalmos. Methimazole was used as first therapeutic option. Initial dose was 0.78mg/kg/day (0.41-2mg/kg/day) average. TSH (57.1%) and FT4 (50%) reached normal values between 6 and 8 months. Remission was observed in 11 patients (34.3%), 3 (9.3%) relapsed, 12 (37.5%) then received treatment with radioiodine (I-131) and 6 (18.7%) continued receiving methimazole. Remission was achieved after 2.81 ± 0.91 years of treatment (range 1.5-4.8), 4.1% after the first year, and 35.3 %, 37.5 % and 25 % respectively after the second, third and fourth year of treatment. Average age of those receiving I-131 was 14.6 years (7.1-19.6 years), at a dose about 7mCi; 75% of them showed remission after 0.64 ± 0.60 year (range 0.16-1.5 years). Conclusions: Hyperthyroidism due to Graves disease is relatively common in children. Remission was obtained in 34.3% of patients treated with methimazole in 2.81 ± 0.91 years average and remission was achieved in 75% of patients treated with I131, in 0.64 + / - 0.60 years average.